Family Iridoviridae Molecular and Ecological Studies of a Family Infecting Invertebrates and Ectothermic Vertebrates - Chinchar, Gregory (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Ranaviruses and other viruses within the family Iridoviridae, infect a wide range of ecologically and commercially important ectothermic vertebrates, i.e., bony fish, amphibians, and reptiles, and invertebrates, including agricultural and medical pests and cultured shrimp and crayfish, and are responsible for considerable morbidity and mortality. Understanding the impact of these various agents on diverse host species requires the combined efforts of ecologists, veterinarians, pathologists, comparative immunologists and molecular virologists. Unfortunately, investigators involved in these studies often work in discipline-specific silos that preclude interaction with others whose insights and approaches are required to comprehensively address problems related to ranavirus/iridovirus disease. Our intent here is to breakdown these silos and provide a forum where diverse researchers with a common interest in ranavirus/iridovirus biology can profitably interact. As a colleague once quipped, "Three people make a genius." We are hoping to do something along those lines by presenting a collection of research articles dealing with issues of anti-viral immunity, identification of a potentially novel viral genus exemplified by erythrocytic necrosis virus, viral inhibition of innate immunity, identification of novel hosts for lymphocystivirus and invertebrate iridoviruses, and modelling studies of ranavirus transmission. Collectively these and others will exemplify the breadth of ongoing studies focused on this virus family.